Rheology of liquid crystalline oligomers for 3-D printing of liquid crystalline elastomers - Bauman, Grant E; Koch, Jeremy A; White, Timothy J (Soft matter, 2022)
Liquid crystalline monomers can be oligomerized and subsequently 3-D printed to prepare liquid crystalline elastomers (LCEs) with spatial variation of the nematic director to create soft materials that undergo complex shape change when subject to stimulus. Here, we detail the correlation of alignment in 3-D printed LCE on the shear history of the oligomeric ink. This coupling is evident both in the polymerization of sheared LCE samples as well as steady-state rheological experiments that quantify the time-dependent flow behaviors of these complex fluids. Under a steady shear flow, oligomeric LC inks transition from a nematic state with unaligned (polydomain) orientation to a uniaxially aligned (monodomain) nematic phase over a large range of applied strain. After cessation of shear flow, the oligomeric LC inks return the polydomain orientation over approximately 30 minutes. The alignment of liquid crystalline segments in the LCE (and the associated stimuli-response of the materials) is ultimately correlated to the degree of strain applied to the ink. A liquid crystalline oligomer displays time-dependent changes in viscosity when subjected to steady shear flow. Temperature and applied shear rate are shown to have an effect on this phenomenon which is relevant to Direct Ink Write printing.